Learning mathematics through Islam Nusantara culture: An etnomathematics study in Indonesia - Rino Richardo; Ahmad Anis Abdullah; Adhetia Martyanti; Dyasih Alin Sholihah; Widha Nurshanti (Universitas negeri Yogyakarta, 2020)
This study discusses the study of Islam Nusantara culture in mathematics learning. This research uses library method. The data obtained is a publication of research articles in a scientific journal. The article analyzed includes three stages, namely organize, synthesize, and identify. The results of data analysis show that (1) culture of Islam Nusantara can be used to teach a concept in learning mathematics, (2) this culture can be used as material in strengthening character education, (3) and this culture can develop the ability of cultural literacy.